Kinetics and mechanism of the oxidation of some cis-Alpha- Phenylcinnamic acids by Pyridinium Chlorochromate (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Oxidation of cis Î±-phenyl cinnamic acids by pyridinium chlorochromate (PCC) was studied in acetic acidâ€“water mixturecontaining perchloric acid. The reaction rate is first order in [PCC] and fractional order in [H+] and has aldehyde as aproduct. The rate of reaction increases with increase in the percentage of acetic acid medium. The reactions exhibit kineticisotope effect. The activation parameters have been evaluated. The added Mn (II) decreases the rate of reaction. Theadded sodium chlorate has no effect on the reaction rate and indicates the absence of ion-ion (or) ion- dipole interaction inthe slow step. The deviation of Hammett plot is noted and a â€œVâ€ shaped curve is obtained.